Investigating the Benefits of Mobile Phone Technology toward the Teaching and Learning Practices at Higher Schools - Nur Rifai Akhsan (Universitas Ahmad Dahlan, 2015)
This article intends to explore the benefits of using M-Learning (mobile phone Learning) to support teaching and learning process for digital immigrant teachers. Digital immigrant teachers are those who want to move from conventional way to more technology enhanced language learning. The exploration on using facilities of mobile learning for classroom teaching will enable teachers to make use of internet access, to pursue their studentsâ€™ technology literacy, to access to a wealth of ready-made ELT materials and to integrate technologies of mobile phone into teaching. The exploration found that the potential uses of mobile phone for learning certainly bring implication for both teacher and students under the issues of technology application literacy, intellectual authority, students-students-teacher collaboration, and teaching and learning reflection and evaluation skill development. Above all, teachers can use many applications of their mobile phone from simple to sophisticated ones. They can use texting facilities (sms) for checking studentsâ€™ work progress, use free social media to give consultation, and many other features that facilitate them to transfer knowledge and help students in learning either in or out of classroom. Certainly, they also need to consider the flaws in mobile phone and keep learning to be familiar with technology development. Furthermore, mobile phone also improve teaching qualities in terms of creating contextual learning outside the classroom, for fieldtrips and for professional development; supporting context-sensitive leaning in non-formal settings, connecting the learning across contexts and human life; making useful learning sites involving technology, people and environment, producing system enabling teacher to deliver quizzes for learning topics, encourage students to practice making theory questions, designing a media board for learners to construct online web pages by sending messages, pictures and audio through their phones, and reaching beyond the traditional settings. Keywords: Mobile phone, teaching and learning, advance technologyÂ